2007
DOI: 10.1021/bi602374m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfated Octa- and Decasaccharides from Squid Cartilage Chondroitin Sulfate E:  Sequencing and Application for Determination of the Epitope Structure of the Monoclonal Antibody MO-225

Abstract: A mixture of octa- and decasaccharides obtained by the digestion with the hyaluronidase of chondroitin sulfate E derived from squid cartilage was subfractionated into 20 and 23 different components, respectively, by anion-exchange HPLC. MALDI-TOF/MS was used to assign the sugar and sulfate composition of the putative octa- and decasaccharides, and a disaccharide composition analysis revealed the building blocks to be A- [GlcUAbeta1-3GalNAc(4S)], C- [GlcUAbeta1-3GalNAc(6S)], and E- [GlcUAbeta1-3GalNAc(4S,6S)] u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The original study by Yamagata et al (64) showed the reactivity of MO-225 with the tetrasaccharides ⌬A-D and ⌬E-D. Recently, Ito et al (65) have shown that MO-225 could strongly react with octasaccharide and larger oligosaccharide fractions derived from CS-D of shark cartilage, and Deepa et al (41) showed that MO-225 reacted with a decasaccharide sequence rich in E units, prepared from squid cartilage CS-E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original study by Yamagata et al (64) showed the reactivity of MO-225 with the tetrasaccharides ⌬A-D and ⌬E-D. Recently, Ito et al (65) have shown that MO-225 could strongly react with octasaccharide and larger oligosaccharide fractions derived from CS-D of shark cartilage, and Deepa et al (41) showed that MO-225 reacted with a decasaccharide sequence rich in E units, prepared from squid cartilage CS-E.…”
Section: Discussionmentioning
confidence: 99%
“…41. b Plus (ϩ) and minus (Ϫ) indicate positive and negative inhibitory activity, respectively, against the binding of GD3G7 to immobilized CS-E in ELISA as described in the legend to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that at least four repeating units of CS-E have the capacity to regulate osteoblast and osteoclast differentiation through distinct mechanisms. In a previous study, it was reported that various oligosaccharides of CS-E enhanced neurite outgrowth 28,29) . Determining the correlation between CS-E oligosaccharide structure and the inhibitory activity on osteoclast formation requires further investigation.…”
Section: Control Cs-c Cs-e Hepmentioning
confidence: 95%
“…CS-K from king crab cartilage was prepared as reported previously (21). The octa-, hexa-, and tetrasaccharides derived from Chn were prepared by treatment with sheep testicular hyaluronidase as described (22).The structurally defined tet-…”
Section: Materials-mentioning
confidence: 99%